A New Stochastic Price Fluctuation Model: Comment - Clark, Peter K. (Review of Economic Studies, 1974)
In a recent note in this Review [1], R. A. Agnew derives some results about mixtures of normal variables and suggests that his new model may be useful as a representation of observed price series in speculative markets. Although his stability result for mixed normal variates is formally correct, it is somewhat tangential to the issue that is generally discussed as stability, and may therefore need clarification.